PFKM phosphorylates histone H3 and promotes mitotic progression by sensing the levels of citrate - Pianpian Lin; Yijun Qi; Huiying Chu; Hongyu Wu; Yajuan Zhang; Xiaolan Huang; Chen Li; Xiaoyan Xu; Hong Gao; Rong Zeng; Guohui Li; Weiwei Yang (Nature Communications)
Abstract Emerging evidence indicates that metabolic signals—including nutrient availability, biosynthetic intermediates, and energy balance—are linked to cell cycle progression. However, how these signals are sensed by the cell cycle machinery remains unclear. Citrate, a key intermediate in the TCA cycle, peaks during mitosis (M phase) and is detected by the glycolytic enzyme ATP-dependent 6-phosphofructokinase 1 muscle isoform (PFKM), accelerating mitotic progression. Mechanistically, citrate binds PFKM, disrupting its tetrameric structure into dimers. Dimeric PFKM interacts with nucleosomes and phosphorylates histone H3 at serine 10 (H3S10), functioning as a protein kinase to promote mitosis and cell proliferation. Structural simulations reveal that PFKM binds nucleosomes optimally when H3S10 aligns with its catalytic site. Disrupting citrate-PFKM or PFKM-H3 interactions reduces H3S10 phosphorylation, delays mitosis, and suppresses tumor growth and T-cell proliferation. Our findings demonstrate that PFKM acts as a citrate sensor, coupling metabolic signals to cell cycle regulation.